Judge's Logical Fallacies And Prospects For The Convict In Supreme Court Decision Number 813 K/PID/2023 - Elya Kusuma Dewi Elya; Muhammad Abdul Aziz; Dyah Adriantini Sintha Dewi; Tanto Lailam; Clarizze Yvoine Mirielle (Universitas Muhammadiyah Surakarta, 2024)
ABSTRACT Purpose of the study: This research scrutinizes the judge's logical fallacy in considering the life history and emotional and psychological condition of the Defendant in Supreme Court Decision Number 813 K/Pid/2023 against the Defendant who was found guilty in a case of premeditated murder, which potentially results in a lighter sentence for the Defendant. Methodology: The research methodology used doctrinal methods. Data were collected, selected, grouped, and arranged in narrative form and analyzed qualitatively. The approach used in this research was a normative approach with legal theory analysis to obtain a complete picture of the judge's considerations in implementing decisions. The analysis utilized was content analysis, i.e., interpreting the meanings intended by and in the judge's considerations in Supreme Court Decision Number 813 K/Pid/2023. Results: The research findings exhibited the life history and social circumstances of the Defendant, who, at that time, served as a member of the Indonesian National Police, with his last position as Kadiv Propam (Head of the Professional and Security Division) who had contributed to the state by contributing to maintaining order and security and upholding the law in the country. The Defendant having served as a member of the National Police for approximately 30 years is a consideration that reduces the sentence. This becomes a logical fallacy for judges, resulting in the impact of public distrust in law enforcement. Applications of this study: The purpose of this research is to elucidate the dynamics of judges' logic in making logical legal considerations in accordance with applicable rules. Keywords: Judge's Consideration, Death Penalty, Court Decision. ABSTRAK Tujuan: Penelitian ini mengkaji kekeliruan pemikiran hakim dalam mempertimbangkan riwayat hidup dan kondisi psikologis emosional terdakwa dalam Putusan Mahkamah Agung Nomor 813 K/Pid/2023 terhadap terdakwa yang dinyatakan bersalah dalam kasus pembunuhan berencana yang berpotensi menyebabkan hukuman yang lebih ringan bagi terdakwa. Metode: Metodologi penelitian menggunakan metode doctrinal, Data dikumpulkan, dipilih, dikelompokkan, dan dirangkai dalam bentuk narasi serta dianalisis secara kualitatif. Pendekatan dalam penelitian ini adalah pendekatan normatif analisis teori hukum sehingga dapat memperoleh gambaran secara lengkap mengenai pertimbangan hakim dalam penerapan putusan. analisis yang digunakan content analysis, yaitu menafsirkan makna-makna yang dimaksud oleh dan dalam pertimbangan hakim dalam Putusan Mahkamah Agung Nomor 813 K/Pid/2023. Hasil: Temuan penelitian menunjukkan bahwa riwayat hidup dan keadaan sosial terdakwa dimana saat itu terdakwa menjabat sebagai Anggota Kepolisian Negara Republik Indonesia dengan jabatan terakhir sebagai Kadiv Propam pernah berjasa kepada negara dengan berkontribusi ikut menjaga ketertiban dan keamanan serta menegakkan hukum di tanah air, Terdakwa telah mengabdi sebagai anggota Polri kurang lebih 30 tahun telah menjadi pertimbangan yang memperingan pemidanaan sebagai kekeliruan hakim dalam berpikir, sehingga dapat menimbulkan dampak ketidakpercayaan masyarakat kepada penegak hukum. Aplikasi penelitian: Kegunaan penelitian ini adalah untuk menjelaskan dinamika logika hakim dalam membuat suatu pertimbangan hukum yang logis sesuai aturan yang berlaku. Kata Kunci: Pertimbangan Hakim, Hukuman Mati, Putusan Pengadilan